SIARAN DENGAN CONTENT POSITIF DAN EDUKATIF - Surianor, Surianor (UIN Antasari Banjarmasin, 2018)
This journal addresses the topic of radio and television broadcasts which are mostly filled with dangdut songs and other events which are sometimes not in accordance with religious norms and regulations in the broadcasting sector. This is indicated by the presence of a number of songs that were hit by reprimand, both by the MUI, the KPID and from the sworddut itself. The problem here is what songs have been broadcast by radio / television and then reprimanded by the authorities, and what songs should be the contents of radio or television broadcasts that are positively charged and educative. This journal is indeed a number of songs that have been banned from being broadcast by radio or television, both because of the lyrics / poetry and the erotic movements of the singers which are categorized as containing pornography and porno-action. Songs should be created and broadcast in line with religious values, customs and regulations, without losing their artistic value, including regional songs. Such songs will be eternal, even though the creator or singer is gone